Новые виды рода Selatosomus (Coleoptera, Elateridae) из горных районов Кавказа и Гиссаро-Дарваза - Долин, В.Г. (Вестник зоологии, 1982)
Four short-winged click-beetle species of the genus Selatosomus (Aphotistus) are described a s new. S. (A.) armenicus sp. n . - similar to S. pecirkanus R t t . and S. violaceus Cd... differs from them by black body and straight mentum; from S. villaceus also differs by longer pronotum, simple thin deep punctulation of the propleura, from S. pecirkanus- by coarse dense punctulation of the pronotum. Type locality: Armenia, Mts. Zangezur, Kadzharan, 2000-2500 m. S. (A.) logoinenkoae sp. n . - similar to S. pecirkanus, differs by the antennal joint. shape, pronotum, and reduced carinae on its hindangles. Type locality : Georgia , Goderdzi pass, ca. 2000 m. S. (A.) persimilis sp. -n. similar to S. mirificus G u r j e v a , distinct by complete loss of pubescence, short second antennal joint, black tarsi etc. Type locality: Tajikistan. Ghissar-Darwaz mountain range. Komarou valley, ca. Novabad, 2400 m. S. (A.) karabachensis sp. n-. similar to S. jajlensis Dolin , differs by short antennaeand the shape of their joints, prosternum and short body pubescence. Type locality: Azerbaijan, Nagornyi Karabakh, Shusha.